Combined Unilateral Hemilaminectomy and Thoracoscopic Resection of the Dumbbell-Shaped Thoracic Neurinoma: A Case Report. (30th August 2012) - Tanaka, Toshihide; Kato, Naoki; Aoki, Ken; Nakamura, Aya; Watanabe, Mitsuyoshi; Tochigi, Satoru; Marushima, Hideki; Akiba, Tadashi; Hasegawa, Yuzuru; Abe, Toshiaki
Abstract : A 41-year-old woman complained of chest pain when coughing. Computed tomography and magnetic resonance imaging disclosed a homogenously enhanced tumor occupying the spinal canal at the Th7 level and extending into the right paravertebral space through the intervertebral foramen between Th7 and Th8. The tumor was successfully removed via a posterolateral approach using unilateral hemilaminectomy followed by thoracoscopic surgery. Since the tumor had a dumbbell shape, a combined approach was considered essential. The histological diagnosis was a thoracic neurinoma. Combined hemilaminectomy and thoracoscopic surgery may be a good alternative for the management of thoracic dumbbell-shaped tumors.